Integrated cognitive behavioral therapy for ADHD in adult substance use disorder patients: Results of a randomized clinical trial. (1st April 2019) - van Emmerik-van Oortmerssen, Katelijne; Vedel, Ellen; Kramer, Floor J.; Blankers, Matthijs; Dekker, Jack J.M.; van den Brink, Wim; Schoevers, Robert A.
Highlights: CBT/Integrated is an integrated CBT treatment directed at SUD and ADHD. CBT/Integrated results in greater reduction of ADHD symptoms than CBT for SUD. CBT/Integrated and CBT for SUD are equally effective in reducing substance use. Abstract: Background: Attention Deficit Hyperactivity Disorder (ADHD) frequently co-occurs with Substance Use Disorders (SUDs). Standard ADHD pharmacotherapies are not effective in patients with this comorbidity and cognitive behavioral therapy (CBT) has not been tested in this population. This RCT aimed to compare the efficacy of Integrated CBT (CBT/Integrated) directed at adult ADHD and SUD with CBT directed at SUD only (CBT/SUD) in patients with SUD and ADHD (SUD + ADHD). Methods: Randomized clinical trial among 119 SUD + ADHD patients in a SUD treatment center. CBT/Integrated consisted of 15 individual sessions of motivational therapy, coping skills training and relapse prevention for SUD, and training of planning skills, problem-solving skills and dealing with emotions for ADHD. CBT/SUD consisted of 10 individual SUD treatment sessions only. Primary outcome was ADHD symptom severity according to the ADHD rating scale (ARS) at post-treatment. Secondary outcomes included ADHD symptom severity after two-month follow-up, and treatment response (≥30% ADHD symptom reduction), substance use, depressive or anxiety symptoms, and quality of life at post-treatment and follow-up. Results: CBT/Integrated was more effective than CBT/SUD in the reduction of ADHD symptoms post-treatment: ARS = 28.1 (SD 9.0) vs. 31.5 (SD 11.4) (F = 4.739, df = 1, 282, p = .030; d = 0.34). At follow-up, CBT/Integrated still resulted in lower ARS scores than CBT/SUD, but the difference was not significant at the 0.05 level. For other secondary outcomes, including substance use, no significant between-group differences were present. Conclusions: Compared to regular SUD cognitive behavioral therapy, integrated cognitive behavioral therapy resulted in a significant extra improvement in ADHD symptoms in SUD + ADHD patients.